From Folk Art To Sustainable Livelihood Case Of A Woman Artisan (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Handicrafts have been one of the major mainstays of the Indian  economy and have subsequently acquired the status of a major  livelihood opportunity for a large number of women in India.  Madhubani paintings are one of the oldest art forms from Mithila region  of Bihar. It is known as Mithila Painting. For centuries, women from the  region of Mithila have been making ritualistic paintings and expressing  their own social world through the medium of paintings. This paper discusses the case and journey of a woman entrepreneur  involved in madhubani paintings and other handicrafts who has not only  fought out of the clutches of poverty but has also impacted the lives of  sixty local women of Muzaffarpur District of Bihar. The present study  aims to understand the role and potential of handicraft sector in  improving and providing a sustainable livelihood option for local  people especially women in the poverty ridden state of Bihar by  strengthening of social capital linkages of women artisans and  production in the homestead site, so that women could be economically  active without leaving the home or being vulnerable to harassment or  violence and empowerment of women as they learn to deal with traders.  The paper also tries to identify the challenges faced by such small  entrepreneurs.
Keywords: Sustainable Livelihood; Handicrafts; Social capital; women entrepreneur